The Value of Student Self-Government in the Process of Self-Realization of Personality - Gutsol, Liudmyla (Pedagogical Discourse, 2014)
The article isdeals with the solving of the problem of self-realization of students in the University. Scientific researches have been analyzed, the objectives, functions, principles, areas of student self-government have been determined. General aspects and importance of student self-government in the process of self-realization have been cleared out, the potential of student self-government in formation of the social mature personality have been revealed, development of managerial, organizational, communicative skills, social activity, civic responsibility and consciousness, harmonic development of students have been explained.